Alleviating mitochondrial myopathy in mice - Erkul, Semin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Mitochondrial dysfunction leads to a myriad of diseases, majority of which are caused due to respiratory chain (RC) deficiencies. Here, we demonstrate further molecular and morphological characterization of a skeletal muscle-specific mitochondrial Aspartyl-tRNA Synthetase (DARS2) knockout mouse model (mKO). The loss of DARS2 in skeletal muscle impaired mitochondrial translation, followed by RC deficiency, activation of adaptive stress responses, defective Complex IV (COX) activity, and reduced oxygen consumption rate. There is currently no cure for mitochondrial myopathy, but supportive methods have proven to be effective in alleviating the manifestation of the disorder. However, the effects of supportive treatments on early-onset mitochondrial myopathy cases and their relevant models remain to be discovered. Following characterization, we focused on the therapeutic effects of the Ketogenic Diet (KD) and 5- aminoimidazole-4-carboxamide ribonucleoside (AICAR) in mKO mice. The KD treatment partially rescued myopathy markers, such as recovery from mitochondrial integrated stress response (ISRmt), increase in COX activity, and eliminated the blockage of autophagic flux without inducing mitochondrial biogenesis and prolonging the lifespan. The analysis of lipid metabolism revealed that DARS2-depleted skeletal muscle is highly dependent on glycolysis for energy production, and KD intervention caused the metabolism to shift further toward glucose utilization. AICAR treatment, on the other hand, induced muscle regeneration, recovery from ISRmt and autophagic block; however, it further reduced COX activity and did not have an effect on mitochondrial biogenesis and lifespan. These findings extend our knowledge of the management of disease phenotypes of mitochondrial translation defects. Significantly, we proved that early-onset severe myopathy manifestation could not be sufficiently alleviated with treatments for mild late- onset myopathies, highlighting the importance of disease- specific treatments.
Keywords: Muscles -- Diseases.; Mitochondria.